2010 3rd International Conference on Computer Science and Information Technology 2010
DOI: 10.1109/iccsit.2010.5565147
|View full text |Cite
|
Sign up to set email alerts
|

An estimate and simulation approach to determining the Automated Guided Vehicle fleet size in FMS

Abstract: One of the many design and control issues of Automated Guided Vehicles System (AGVS) is the AGV fleet size. This paper presents a new solution method to determining the number of vehicles in the AGVS based on FlexibleManufacturing System (FMS). The approach relies on two procedures-estimate and simulation. With estimate procedure, the mathematic method will be used to estimate the AGV fleet size. In the next procedure, the estimate value will be used in the simulation model of AGVS for further study. The relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In the first stage, they estimated the required number of AGVs with the mathematical model and reduced the computation time, since they utilized the output as the simulation input. They reported that the fleet size estimation for multi-loaded AGVs with the heuristic method was not accurate when compared to real-life requirements; however, simulation methods led to a better solution [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the first stage, they estimated the required number of AGVs with the mathematical model and reduced the computation time, since they utilized the output as the simulation input. They reported that the fleet size estimation for multi-loaded AGVs with the heuristic method was not accurate when compared to real-life requirements; however, simulation methods led to a better solution [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The objective of their method was to minimize the travel time or overall cost. Yifei et al [37] developed analytical and simulation methods simultaneously to find the optimum number of AGVs in a flexible manufacturing system. Pjevcevic et al [38] designed a decision-making approach based on data envelopment analysis to determine the fleet size of AGVs at a port container terminal.…”
Section: Agv Fleet Sizing and Assignmentmentioning
confidence: 99%
“…Other studies use two-stage approaches for system simulation and evaluation, or they develop case studies to determine fleet size and evaluate the impacts on indicators, such as queue sizes, occupation numbers, and service times [8,27]. In healthcare, simulation models are used to evaluate supply chain performance of AGV-based material handling systems versus manual delivery systems [22,21,2].…”
Section: Introductionmentioning
confidence: 99%